Analysis of Sarcasm Language Use on Instagram Social Media (Case Study of Students from the Faculty of Social Sciences UINSU) - Yasmin, Adelina Putri; Zuhriah, Zuhriah (CV. ITTC INDONESIA, 2024)
This article aims to examine the dynamics of sarcasm language use by students of the Faculty of Social Sciences at the State Islamic University of North Sumatra (UINSU) in their interactions on Instagram social media. The urgency of this research arises from the observation that sarcasm, although often used as a communication tool, frequently leads to misinterpretations and interpersonal conflicts in the digital context that lacks non-verbal cues. This study adopts a qualitative case study approach with a constructivist paradigm, using thematic analysis techniques to interpret data obtained through in-depth interviews and observation of social media activities. Data validity testing was conducted through source triangulation to ensure the reliability of the findings. The research results indicate that students have significantly varied understandings of sarcasm, which is often misinterpreted as serious communication, leading to undesired emotional reactions. In the segment